The eye - Wagner, Paula; Granger, Don; Manning, Michelle; Moreau, David; Palud, Xavier; Lionsgate; Paramount Vantage; Vertigo Entertainment ([Santa Monica, California] : Lions Gate Films/ Paramount Vintage, 2008)
The violinist Sydney Wells has been accidentally blinded by her sister Helen since she was five years old. She submits to a surgery of cornea transplantation, and while recovering from the operation, she realizes that she is seeing dead people. With the support of Dr. Paul Faulkner, Sidney finds who the donor of her eyes was and they travel to Los Llanos in Mexico to resolve the mystery of her visions
Title from title screen
Director of photography, Jeffrey Jur ; editor, Patrick Lussier ; music, Marco Beltrami ; costume designer, Michael Dennison ; production designer, James Spencer ; visual effects supervisors, Mike Uguccioni, Marc Varisco
Cast: essica Alba, Alessandro Nivola, Parker Posey, Rade Serbedzija, Fernanda Romero, Rachel Ticotin, Obba Babatundé, Danny Mora, Chloe Moretz
VCD format
Keywords: Horror films; Cornea -- Transplantation -- Drama; Blind women -- United States -- Drama; Supernatural -- Drama